2017
DOI: 10.1103/physrevb.96.104305
|View full text |Cite
|
Sign up to set email alerts
|

Universality of electronic friction: Equivalence of von Oppen's nonequilibrium Green's function approach and the Head-Gordon–Tully model at equilibrium

Abstract: For a molecule moving near a single metal surface at equilibrium, following von Oppen et al (Beilstein J. Nanotechnol, 3, 144 (2012)) and using a non-equilibrium Green's function (NEGF) approach, we derive a very general form of electronic friction that includes non-Condon effects. We then demonstrate that the resulting NEGF friction tensor agrees exactly with the Head-Gordon/Tully (HGT) model, provided that finite temperature effects are incorporated correctly. The present results are in agreement with our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…Furthermore, we have shown that non-Condon effects can be easily included into a nonequilibrium electronic friction. Thus, given our previous work proving that, at equilibrium, the QCLE friction agrees with the Head-Gordon-Tully model as well as many other forms of electronic friction, 46,50,51,55,65 we believe there is now very strong proof that, in the limit of Markovian dynamics, there is only one, universal electronic friction associated with the Born-Oppenheimer approximation in the adiabatic limit. Future work must address how to incorporate non-Markovian effects efficiently; is there an optimal approach or many different approaches depending on the Hamiltonian?…”
Section: A a Single Level With A Harmonic Oscillatormentioning
confidence: 52%
“…Furthermore, we have shown that non-Condon effects can be easily included into a nonequilibrium electronic friction. Thus, given our previous work proving that, at equilibrium, the QCLE friction agrees with the Head-Gordon-Tully model as well as many other forms of electronic friction, 46,50,51,55,65 we believe there is now very strong proof that, in the limit of Markovian dynamics, there is only one, universal electronic friction associated with the Born-Oppenheimer approximation in the adiabatic limit. Future work must address how to incorporate non-Markovian effects efficiently; is there an optimal approach or many different approaches depending on the Hamiltonian?…”
Section: A a Single Level With A Harmonic Oscillatormentioning
confidence: 52%
“…At equilibrium, due to time reversal symmetry, the friction tensor is symmetric (along with respect to α and ν) and positive definite 63,68,70 , such that there is always a dissipated work associated with driving, i.e. Ẇ (2) > 0.…”
Section: B Nonadiabatic Corrections To Thermodynamics Quantitiesmentioning
confidence: 99%
“…Furthermore, according to the QCLE (and many other approaches 35,39,40,47,48 ), the correct electronic friction term is not given by Eq. (7), but rather also involves the spectral function (such that broadening is again included)…”
Section: Article Scitationorg/journal/jcpmentioning
confidence: 99%